The novel GLP‐1‐gastrin dual agonist, ZP3022, increases β‐cell mass and prevents diabetes in db/db mice. Issue 1 (9th September 2012) - Fosgerau, K.; Jessen, L.; Lind Tolborg, J.; Østerlund, T.; Schæffer Larsen, K.; Rolsted, K.; Brorson, M.; Jelsing, J.; Skovlund Ryge Neerup, T.
Abstract Aim Diabetes is characterized by β‐cell deficiency, and therefore restoration of β‐cell function has been suggested as a potential therapy. We hypothesized that a novel glucagon‐like peptide‐1 (GLP‐1)‐gastrin dual agonist, ZP3022, improves glycaemic control via improvement of β‐cell status in db/db mice. Methods Diabetic mice were studied following short‐ or long‐term treatment with either the GLP‐1‐gastrin dual agonist or the commercially available GLP‐1 agonists (exendin‐4 and liraglutide). The effects on glycaemic control were addressed by repeated glucose tolerance tests and/or measurements of HbA1c levels, and pancreatic islet and β‐cell masses were determined by stereology. Results ZP3022 and the pure GLP‐1 agonists improved glycaemic control after both short‐ and long‐term treatment compared with vehicle. Interestingly, the effect was sustainable only in mice treated with ZP3022. Stereology data displayed a dose‐dependent increase of β‐cell mass (p < 0.05) following treatment with ZP3022, whereas no significant effect of liraglutide was observed (β‐cell mass: vehicle 3.7 ± 0.2 mg; liraglutide (30 nmol/kg) 3.4 ± 0.5 mg; ZP3022 (30 nmol/kg) 4.3 ± 0.4 mg and ZP3022 (100 nmol/kg) 5.2 ± 0.4 mg). Conclusion The novel GLP‐1‐gastrin dual agonist, ZP3022, improved glycaemic control in db/db mice, and pancreatic islet and β‐cell mass increased significantly following treatment with ZP3022 compared with vehicle.